Modeling price and demand interaction in inventory systems - İşlier, Bekir Turgut. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
In this thesis, we examine the impact of price on demand in inventory systems with one and two suppliers. We present two models. In the first model, price determines the probability of demand occurrence. In case demand occurs, its amount is random and independent of the price. In the second model, price determines the distribution of the amount of demand by governing the purchasing probability of each potential customer. In both models, we try to nd the order amount and the price that maximize the average one-period profit. We discuss how the optimal policy and the profit change with respect to the parameters related to cost, demand and the relationship between price and demand. Under each of the models, we present a variation in order to account for supply uncertainty. We discuss the benefit of taking the capacity constraints into account, and demonstrate the effect of parameters related to the capacity constraint on the optimal policy and profit.
Keywords: Inventory models.